Peroral endoscopic myotomy (POEM) for dysphagia and esophageal motor disorder after antireflux fundoplication - Gonzalez, Jean-Michel; Monino, Laurent; Ah-Soune, Philippe; Vitton, Véronique; Barthet, Marc (Endoscopy, 2020)
Introduction Laparoscopic fundoplication is the treatment of severe and refractory gastroesophageal reflux disease (GERD). It induces dysphagia in 5 % – 10 % owing to a tight valve ± esophageal motility disorders (EMD), with challenging management. We assessed the first case series assessing peroral endoscopic myotomy (POEM) in such a situation. Methods A retrospective case series including eight patients with severe dysphagia after laparoscopic fundoplication who were treated by POEM. They were assessed clinically by Eckardt and Mellow – Pinkas dysphagia scores, and by high resolution manometry (HRM). The procedure was a regular esophageal POEM, mainly posterior, including a myotomy of the wrap. The objectives were to evaluate the clinical efficacy, technical difficulties, and complications of this approach. Results HRM showed aperistalsis in 6 /8 patients and raised lower esophageal sphincter (LES) pressure in 5 /8. The median preoperative Eckardt and dysphagia scores were 5 and 3.5, respectively. The procedure was completed in 7 /8 patients, with a clinical efficacy rate (normalization of both scores) of 75 % (6 /8). Although the submucosa seemed more fibrotic and vascularized, no severe complications occurred. Conclusion POEM is a newly described therapeutic option to consider for managing dysphagia due to EMD after laparoscopic fundoplication.